2006
DOI: 10.1080/0028825x.2006.9513028
|View full text |Cite
|
Sign up to set email alerts
|

Subalpine gully‐head ribbon fens of the Lammerlaw and Lammermoor Ranges, Otago, New Zealand

Abstract: Vegetation patterns of subalpine gullyhead mires were investigated in the flat-topped Lammerlaw and Lammermoor Ranges, South Island, New Zealand. Two intensively studied mires each consist of a series of peaty terraces and scarps. Terraces may contain pools, elongated downslope in the narrow, lower altitude mire, but across slope in the broader, upper mire. A crest occurs on some terrace lips, and marginal "spillways" (channel-like zones) occur down some scarps. Some mires have drained by subsurface pipes.Vege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Soil pipes are significant subsurface structural features of peatlands and are known to occur in northern Europe, North America, Siberia, and the Southern Hemisphere [ Norrström and Jacks , 1996; Price , 1992; Rapson et al , 2006; Thorp and Glanville , 2003]. They have been widely recorded in UK blanket peats [e.g., Holden and Burt , 2002; Holden , 2005; Jones et al , 1997], where it has been shown that peat drainage, surface drying and Calluna vulgaris L.…”
Section: Introductionmentioning
confidence: 99%
“…Soil pipes are significant subsurface structural features of peatlands and are known to occur in northern Europe, North America, Siberia, and the Southern Hemisphere [ Norrström and Jacks , 1996; Price , 1992; Rapson et al , 2006; Thorp and Glanville , 2003]. They have been widely recorded in UK blanket peats [e.g., Holden and Burt , 2002; Holden , 2005; Jones et al , 1997], where it has been shown that peat drainage, surface drying and Calluna vulgaris L.…”
Section: Introductionmentioning
confidence: 99%
“…Larger pipes have also been commonly reported in peatlands (e.g. Jones, ; Markov and Khoroshev, ; Woo and DiCenzo, ; Price, ; Norrstrom and Jacks, ; Jones et al ., ; Glaser, ; Gunn, ; Holden and Burt, ; Thorp and Glanville, ; Holden et al ., ; Holden, ; Rapson et al ., ). Soil conditions are generally too harsh for burrowing fauna in most peatlands, but peatlands may be conducive to piping because they are susceptible to rapid desiccation cracking.…”
Section: Introductionmentioning
confidence: 99%
“…Work by , 2004 has been pioneering in consistently addressing the FBT. Practical experimentation, such as that initiated in bogs by Clymo (1965) and Bellamy & Reiley (1967), and more recently demonstrated by Scheffer et al (2001), Heijmans et al (2002 and Adema et al (2006), offers much needed insight into bog mechanics.…”
Section: Resultsmentioning
confidence: 99%
“…A peat accumulating system or zone is a prerequisite, but it is otherwise far from clear how the process occurs (Hughes 2000;Hughes et al 2000Hughes et al , 2007Hughes & Dumayne-Peaty 2002;, 2004.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation